(untitled) (Research, Society and Development, 2020)
Botulism presents as a bacterial infection, neuroparalytic and non-contagious infection caused by toxins produced by Clostridium botulinum, called botulinum toxins. However, even though this disease has a high lethality, there is a great lack of epidemiological studies on this topic in Brazil. Based on that, this research aimed to trace the epidemiological profile of botulism in Brazil between the years 2008 to 2018. It is an epidemiological, retrospective, analytical and documentary study, in which data were collected from the Department of Informatics of the Unified Health System. Between 2008 and 2018, 69 cases of botulism confirmed in Brazil were evidenced, with the state of São Paulo having the highest number of notifications (30.5%). The profile of those affected was mostly male (58%), low education (26%), 20 to 39 years old (47.8%), white ethnicity (59.4%), residents of the urban area ( 85.5%), contracted botulism, mainly food-type (94.2%), with the presence of AB toxins (15.9%) and clinical cure outcome (68.1%). Thus, the data present in this research can contribute to the development of indicators and public policies related to botulism.